Evaluationof fracture toughness ofalpha-Nb5Si3 by micro-sized cantilever beam testing. Issue 1760 (18th February 2015) - Suzuki, Shiori; Sekido, Nobuaki; Ohmura, Takahito; Miura, Seiji
ABSTRACT: A micro-sized fracture testing method has been applied to investigate fracture toughness of alpha-Nb5 Si3 . Chevron-notched single crystal specimens with a size of 3 x 3 x 15 μm 3 were prepared in a grain of polycrystalline alpha-Nb5 Si3 by focused ion beam, FIB, technique. Fracture tests were conducted using a nanoindenter at room temperature and linear load-displacement curves and smooth fracture surfaces were obtained. This fracture behavior was presumed to be brittle fracture similar to bulk alpha-Nb5 Si3 . The average of fracture toughness K Q is 3.45 ± 0.29 MPa√m under a small-scale yielding condition.